Influence of different patient positions on erector spinae plane block spread in modified radical mastectomy: a prospective randomized comparative study - Adel Ibrahim Hozien; Sahar Ahmed Elkaradawy; Hussein M. Agameya; Walid M. Ahmed; Ahmed F. Elsosy (BMC Anesthesiology)
Abstract Background Although the analgesic effect of erector spinae plane block (ESPB) has been proven, its efficacy may be influenced by the patient’s position during the block. Methods We randomly allocated forty patients undergoing unilateral modified radical mastectomy (MRM) with axillary lymph node dissection to receive preoperative ESPB in sitting (Group 1) or lateral position (Group 2), and the patient was kept in position for 15 min, either in the high Fowler’s or lateral position. The primary outcome was the dermatomal sensory block and radiocontrast material spread by Computed Tomography (CT) 15 min after the block. Secondary outcomes were the visual analog scale for pain (VAS), opioid consumption, patient satisfaction, and complications. Results There was a significant increase in the dermatomal sensory block in Group 1 compared to Group 2 at midaxillary (confidence interval (C.I) 95% = 0.55, p-value = 0.006) and scapular lines (95% C.I = 0.50, p-value = 0.014); meanwhile, there were insignificant differences at the parasternal and midclavicular lines (p-value = 0.232 and 0.201 respectively). Early CT showed more craniocaudal contrast distribution in a higher percentage of patients in Group 1, with a higher incidence of spread to paravertebral/epidural spaces (though not statistically significant). The VAS, morphine consumption, and patient satisfaction were comparable. Conclusion The ESPB in the sitting position provided a more significant posterolateral sensory block. The CT evidence of early paravertebral and epidural spread was observed more often in the sitting group, but without statistical significance. ESPB in both patient positions produced comparable postoperative analgesia. Trial registration Pan African Clinical Trials Registry (PACTR) (PACTR202204720116048) on 27/04/2022.